LANDSCAPE ARCHITECTURE BY MACRO OUTLINE: CROSSING AGRICULTURAL SCIENCES AND GEOGRAPHY FROM BRAZIL - de Souza Silva, Rafael (REVISTA DE AGRICULTURA, 2024)
Through an approach of landscape, this paper organizes one of the scales gathered and questioned as “outlines”. This term has contained polysemous mindset, as much carrying it several viewpoints and diversity of perspectives. Also, Landscape Architecture professionally constructed “bridges” between natural sites and urban sights and, wilderness is one of ground concepts to Brazilian Conversation Units (UCs) and biological reserves from Brazil. Thereby, this literature analysis focus on political, historical and spatial aspects to cross Agricultural Sciences and Geography.